Jenis-jenis Tumbuhan yang Dimanfaatkan sebagai Obat Tradisional di Kecamatan Lubuk Tarok Kabupaten Sawahlunto Sijunjung - Darmanella Dian Eka Wati (Eduscience Development Journal, 2019)
The government strives to realize development in the field of health as a whole, integrated and affordable by all levels of society through the "back to nature" program, supporting the government's efforts, one of which is by collecting data on the types of traditional medicinal plants. Lubuk Tarok District has a diversity of traditional medicinal plants. To find out the types of plants that are used as traditional medicine and their uses in traditional medicine in Lubuk Tarok Subdistrict, Sijunjung Regency, the authors conducted a study in Lubuk Tarok Subdistrict in Agurtus-September 2004. This research is descriptive by using a population of all types of plants that are used as traditional medicine in Lubuk Tarok District. Samples taken in the form of plants used as traditional medicine are known from the results of interviews with commonly known shamans and housewives over 50 years of age in the three kenagarians namely Kenagarian Lalan, Kenagarian Lubuk Tarok, and Kenagarian Buluh Kasok.The results of the study found 117 types of plants that were used as traditional medicines including 45 tribes and 103 genera with their habitus of 42 types of herbs, 38 species of shrubs, 30 species of trees, 2 types resembling trees, 4 types of calmus and 1 type of calamus. which have been cultivated are 63 species and 43 species have been used in the pharmaceutical industry while 54 species are wild. These traditional medicinal plants are used in the treatment of diseases categorized into 31 types of diseases, and are generally used in the form of herbs. The most used organ is leaves.